Effects of different dentin thicknesses and air cooling on pulpal temperature rise during laser welding - SEÇİLMİŞ, ASLI; Bulbul, Mehmet; Sari, Tugrul; Usumez, Aslihan (My University, 2013)
The neodymium/yttrium-aluminum-garnet (Nd/YAG) laser has been suggested to repair broken prostheses in the mouth. This study investigated the effects of different dentin thicknesses and air cooling on pulpal temperature rise during laser welding. Three intact human maxillary molars were prepared for full-veneer crown. For each tooth, dentin thicknesses in mesiobuccal cusp was 2, 3, or 4 mm. Twenty dies were duplicated from each of the prepared teeth. For metal copings with 0.5-mm thickness, wax patterns were prepared with dip wax technique directly onto each of dies. All patterns were sprued and invested. The castings were made using a nickel-chromium alloy (Nicromed Premium, Neodontics). A hole with 0.5-mm diameter was prepared on the mesiobuccal cusp of each crown. The Nd/YAG laser (9.85 W; 1 Hz repetition rate; fluence, 1.230 J/cm(2); Fidelis Plus 3, Fotona) was used for welding with or without air cooling (n = 10). The temperature rise was measured in pulpal chamber with a J-type thermocouple wire that was connected to a data logger. Differences between start and highest temperature reading were taken, and temperature rise values were compared using two-way analysis of variance and Tukey-s honestly significant difference tests (alpha = .05). Pulpal temperature rise varied significantly depending on the dentin thickness and air cooling (p 0.05); however, pulpal temperature rise was the lowest for 4-mm dentin thickness group (p < 0.05). The highest values of thermal increase were found in the pulp chamber (6.8A degrees C) when no air cooling was used in 2-mm dentin thickness group. Laser welding on base metal castings with Nd/YAG laser can be applied with air cooling to avoid temperature rises known to adversely affect pulpal health when dentin thickness is 2 or 3 mm.